Connecting the British Pacific: Naval surgeons in the mid-nineteenth century Pacific - OH, H (2020)
This thesis examines British naval medical officers’ observations of Pacific geographies, environments, peoples and societies, drawing on the official and private records produced during their naval service. It argues that naval surgeons produced the British Pacific in the mid-nineteenth century. The British Pacific was connected by naval officers, including surgeons, who developed a collecting and corresponding network in collaboration with Kew Gardens. The naval contribution to this Pacific network was considerable, but at the same time, the network included non-naval contributors. The role of the Navy was crucial within this network because its surgeons were one of the first cadres that conceptualized Pacific geography: they not only mapped the lands and coastlines but also produced meanings for each place that defined its relationship to Britain and the Empire. Hence, the British Pacific was shaped by both physical boundaries and produced meanings. Also, naval surgeons’ observations and activities in each naval station show that they were, in various ways, connected to metropolitan Britain and its society. Focusing on the idea of the Pacific as a vulnerable, risky and unstable place, this thesis shows how naval surgeons coped with this space and turned it to the ‘British Pacific’.